Smartphone repairability indexes in practice: Linking repair scores to industrial design features. - Barros, Mário; Dimla, Eric (Journal of Industrial Ecology, 2023)
Policymaking mediates the relationships between manufacturers and consumers, thus defining the boundaries for the philosophies of production set forth by major companies. Research states that policymaking falls short in addressing the waste issues, natural resources consumption, greenhouse gas emissions, and other negative impacts posed by premature obsolescence; only recently have the "right‐to‐repair" guidelines demanded by environmental organizations and communities of citizens been included in policymaking. The introduction of the Index of Repairability in France as information at the point of sale aims to inform consumers and support their decision‐making in purchasing more repairable products. In this paper, we consider the two Indexes of Repairability publicly available to consumers—in the French legislation and iFixit—and assess their application to smartphones from three manufacturers. The study establishes links between the scores and the industrial design features that promote or hinder repairability, service factors and information for self‐repair, authorized repair, and independent repair. Data collection considers the available information for consumers and citizens by using netnography and secondary data from manufacturers, policymakers, and communities of users. Our findings suggest that higher scores that indicate easier repairability are not limited to product architectures that follow design for disassembly guidelines. Smartphones that are difficult to repair can still score high, and thus be perceived as easier to repair, if manufacturers provide high quality and affordable service. This paper discusses the results of the ongoing development of repairability scores for smartphones, thus suggesting paths for future research to improve methods and policies to support a longer lifetime of products.